13-6(x+3)=12-5(x+4)

Simple and best practice solution for 13-6(x+3)=12-5(x+4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13-6(x+3)=12-5(x+4) equation:


Simplifying
13 + -6(x + 3) = 12 + -5(x + 4)

Reorder the terms:
13 + -6(3 + x) = 12 + -5(x + 4)
13 + (3 * -6 + x * -6) = 12 + -5(x + 4)
13 + (-18 + -6x) = 12 + -5(x + 4)

Combine like terms: 13 + -18 = -5
-5 + -6x = 12 + -5(x + 4)

Reorder the terms:
-5 + -6x = 12 + -5(4 + x)
-5 + -6x = 12 + (4 * -5 + x * -5)
-5 + -6x = 12 + (-20 + -5x)

Combine like terms: 12 + -20 = -8
-5 + -6x = -8 + -5x

Solving
-5 + -6x = -8 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-5 + -6x + 5x = -8 + -5x + 5x

Combine like terms: -6x + 5x = -1x
-5 + -1x = -8 + -5x + 5x

Combine like terms: -5x + 5x = 0
-5 + -1x = -8 + 0
-5 + -1x = -8

Add '5' to each side of the equation.
-5 + 5 + -1x = -8 + 5

Combine like terms: -5 + 5 = 0
0 + -1x = -8 + 5
-1x = -8 + 5

Combine like terms: -8 + 5 = -3
-1x = -3

Divide each side by '-1'.
x = 3

Simplifying
x = 3

See similar equations:

| n(n+2)=399 | | w-8=0 | | 3.00(20+x)= | | 9x-(3x+30)=12 | | 23+2y-9=11y-14-5Y | | 105n=-140n | | .17(1.2)= | | 4(a-2)=3a | | 22-7x=111 | | -3(t-1)+6t=5t-1 | | 3(x-4)=8x-5-5x | | 7x+2-x=5+5x-2 | | -6x^2-10=0 | | 6x+4=4(x+3) | | -3x+5+4x=-5+22 | | 10=-6x^2 | | 6-4y=11-8y+4y | | 4x^7+6x^2=0 | | 20x-6=50x+12 | | 36-8m=8m-7m | | y+2.5=-8.5-7.6 | | -3x+21=4x | | 1320=-2x+1200 | | 1320=6x | | 5d^2-45=0 | | x^2-12x-12=0 | | 5u+4.6=10.6 | | -5y-1(5y-9)=1+2(8-y) | | 6(x+9)+2=-8(x-7)-9 | | 5(5y+4)-17=6(3y-3)-7 | | 4(3x+21)=24 | | 5x+1=4(x+5)+9 |

Equations solver categories